How managerial ties impact opportunity discovery in a transition economy? Evidence from China. Issue 2 (16th December 2019) - Guo, Hai; Tang, Jintong; Wei, Zelong
Abstract : Purpose: By integrating the resource management perspective and the optimal distinctiveness perspective, the purpose of this paper is to explain how firms configure their managerial ties and competences to identify entrepreneurial opportunities. Design/methodology/approach: Using survey data collected from 238 firms in a transition economy, this paper tests a model of firms' exploration and exploitation competences under which managerial ties promote or constrain opportunity discovery. Findings: The paper finds that managerial ties are positively related to opportunity discovery. More importantly, competence exploration strengthens the impact of business ties on opportunity discovery, whereas it weakens the impact of political ties. On the contrary, competence exploitation strengthens the effect of political ties on opportunity discovery, whereas it weakens the impact of business ties. Originality/value: First, the findings enrich the social network perspective of opportunity recognition by linking managerial social ties to opportunity discovery in the context of a transition economy. Second, this paper adds to current understanding of the resource management perspective and the optimal distinctiveness perspective by exploring the fit between different managerial ties (business ties vs political ties) and different competences (exploration vs exploitation) in contributing to opportunity discovery.